Survival Analysis Of Dry Eye Disease Related To The Bleb Morphology In Primary Glaucoma Patient Post Trabeculectomy: Oral Presentation - Observational Study - Resident - MELISA ESTER LETARENI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dry eye disease (DED) has a prevalence of approximately 40-59% of all glaucoma patients. Changes in cellular structure after trabeculectomy underlie the instability of the tear film. This study aims to determine the relationship between DED and post-trabeculectomy bleb morphology. Methods : An observational study with survival analysis design to evaluate the time to DED in primary glaucoma patients with post- trabeculectomy blebs was undertaken at the Eye Health Polyclinic of Mohammad Hoesin Hospital Palembang from January to March 2022. There were 30 primary glaucoma patients who met the inclusion criteria. Bivariate analysis to determine the relationship between bleb morphology and DED was analyzed using the Fisher Exact test. DED survival analysis was conducted using Kaplan Meier analysis. Results : Three months after trabeculectomy, 11 of 30 (36.7%) patients suffered from DED. There was a significant relationship between bleb height and DED three months after trabeculectomy [PR = 14.222 (Cl 95% 2.324- 87.028; p = 0.004)]. In addition, the results showed that there was a significant difference in the survival time of DED in glaucoma patients based on bleb height (p = 0.001). Conclusion : Bleb height is a predictor of DED in glaucoma patients after trabeculectomy.